2021
DOI: 10.3390/ph14090836
|View full text |Cite
|
Sign up to set email alerts
|

LRP1B: A Giant Lost in Cancer Translation

Abstract: Low-density lipoprotein receptor-related protein 1B (LRP1B) is a giant member of the LDLR protein family, which includes several structurally homologous cell surface receptors with a wide range of biological functions from cargo transport to cell signaling. LRP1B is among the most altered genes in human cancer overall. Found frequently inactivated by several genetic and epigenetic mechanisms, it has mostly been regarded as a putative tumor suppressor. Still, limitations in LRP1B studies exist, in particular as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 123 publications
1
42
0
Order By: Relevance
“…In chronic lymphocytic leukaemia (CLL), IGLL5 mutations were associated with a trend towards decreased overall gene expression, and patients bearing IGLL5 mutations were suggestive for the low-risk of CLL [ 35 ], which to some extent, was consistent to our result showing that IGLL5 mutated pGI-DLBCL patients had a better OS. On the other hand, LRP1B is giant membrane molecule that is among the most altered genes in human malignancies [ 36 ]. Functional studies have confirmed that LRP1B expression in cancer cells could reduce in vitro cell proliferation and migration abilities, and also suppress in vivo tumorigenicity in mouse models [ 37 – 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In chronic lymphocytic leukaemia (CLL), IGLL5 mutations were associated with a trend towards decreased overall gene expression, and patients bearing IGLL5 mutations were suggestive for the low-risk of CLL [ 35 ], which to some extent, was consistent to our result showing that IGLL5 mutated pGI-DLBCL patients had a better OS. On the other hand, LRP1B is giant membrane molecule that is among the most altered genes in human malignancies [ 36 ]. Functional studies have confirmed that LRP1B expression in cancer cells could reduce in vitro cell proliferation and migration abilities, and also suppress in vivo tumorigenicity in mouse models [ 37 – 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…LRP1B , member of the LDL receptor family, is a large gene located on chromosome 2q, containing more than 91 exons and spanning over 500 kb. The related protein is 4599 amino acids long [ 21 ] and it is involved in a large functional spectrum, ranging from receptor-mediated endocytosis, lipoprotein trafficking, transportation of nutrients and vitamins, developmental processes to cellular signaling [ 22 ]. LRP1B is one of the most altered genes in human cancer overall [ 22 ] and its role has been closely related to cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…The related protein is 4599 amino acids long [ 21 ] and it is involved in a large functional spectrum, ranging from receptor-mediated endocytosis, lipoprotein trafficking, transportation of nutrients and vitamins, developmental processes to cellular signaling [ 22 ]. LRP1B is one of the most altered genes in human cancer overall [ 22 ] and its role has been closely related to cancer progression. LRP1B gene was identified as commonly inactivated in non-small-cell lung cancer cell lines and its inactivation by several genetic and epigenetic mechanisms has been frequently reported in multiple tumor types [ 22 ], corroborating its proposed tumor suppressor function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LRP1B is a putative tumor suppressor gene, and its mutation status has been found to be associated with enhanced cell proliferation and colony formation in various cancers. 26 In CLL, whole exome analysis showed that LRP1B mutation affected 5% of the patients, but its role is not fully understood. 27 …”
Section: Discussionmentioning
confidence: 99%